2006
DOI: 10.1016/j.jacc.2006.05.080
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Noninvasive Coronary Angiography With Multi-Slice Computed Tomography and Myocardial Perfusion Imaging

Abstract: Myocardial perfusion imaging and MSCT provide different and complementary information on CAD, namely, detection of atherosclerosis versus detection of ischemia. As compared to invasive angiography, MSCT has a high accuracy for detecting CAD in patients with an intermediate likelihood of CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
213
1
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 429 publications
(235 citation statements)
references
References 24 publications
14
213
1
7
Order By: Relevance
“…While not a focus of this systematic review, several studies have attempted to examine CCTA's ability to diagnose functional cardiac deficits, using SPECT or another functional test as a reference. 2,74,75 While negative predictive value for these abnormalities was similar to that reported in the ICA-reference studies, positive predictive value only ranged between 50-60%, which is indicative of overestimation of clinically significant obstruction by CCTA. Some have posited that, with increasingly precise technology, the ability to use CCTA to study blood flow and perfusion deficits will be heightened; evidence has not yet accumulated to evaluate this hypothesis.…”
Section: Discussionsupporting
confidence: 76%
“…While not a focus of this systematic review, several studies have attempted to examine CCTA's ability to diagnose functional cardiac deficits, using SPECT or another functional test as a reference. 2,74,75 While negative predictive value for these abnormalities was similar to that reported in the ICA-reference studies, positive predictive value only ranged between 50-60%, which is indicative of overestimation of clinically significant obstruction by CCTA. Some have posited that, with increasingly precise technology, the ability to use CCTA to study blood flow and perfusion deficits will be heightened; evidence has not yet accumulated to evaluate this hypothesis.…”
Section: Discussionsupporting
confidence: 76%
“…31,32 Most prior studies that have evaluated the clinical utility of coronary CTA in symptomatic low to intermediate risk ED patients have been limited by sample size, 21,22,24,25,27 short follow-up periods, 22,24,28 or use of concurrent diagnostic tests for clinical decisionmaking. 23,33 Hoffman et al 24 studied 103 admitted intermediate risk patients and found that 73 patients without significant coronary disease on coronary CTA had a 100% negative predictive value for ACS during index hospitalization, as well as for major adverse cardiac events after 5 months. Rubinshtein et al 25 found a 100% negative predictive value for the ED diagnosis of ACS in 58 patients.…”
Section: Discussionmentioning
confidence: 99%
“…13 In a single-center trial that enrolled 108 subjects with suspected coronary artery disease, Dewey et al showed that MSCT was more specific in viewing the coronary lesions compared to MRI; however, due to latest developments in CMR, its diagnostic precision has gradually improved in the last years. 14 The ability of CMR to detect information on ischemia induced by stress and myocardial viability are extremely important in making the best possible therapeutic decision and to improve the outcome of subjects with MI.…”
Section: Cmr Versus Msct Coronary Angiographymentioning
confidence: 99%